Lifestyle associated to self-esteem and demographics variables in nursing students - Silva Fhon, Jack Roberto (2019)
Objective: To verify the association between lifestyle with self-esteem and demographic variables to the nursingstudents at a private university. Methods: Quantitative, descriptive and cross-sectional research with 183 studentsfrom second to fourth year of nursing. We used the demographic instrument, Self-Esteem Inventory – Adults(Form C) and Lifestyle instrument. For data analysis we used descriptive statistic, Pearson correlation and Chisquare test (p<0.05). Results: 79.2% were women, 84.2% were married, 69.9% worked. 41.5% reported to havea medium high self-esteem and 53.6% had healthy lifestyle. We didn’t find correlation between life styles and theage to de student. We verified the association between the lifestyle levels and self-esteem levels. Conclusion: Wefound there is association between lifestyle and self-esteem in the nursing student.